The Role of Clinical Genetic Analysis in Predicting the Risk of Retinal Vein Occlusion - Zuhriddinovna, Jalalova Dilfuza; Aziza, Odilova (American Journal of Biomedicine and Pharmacy, 2025)
Retinal vein occlusion (RVO) represents a prevalent retinal vascular disorder that can result in substantial visual impairment if left unrecognized. Emerging evidence highlights the influence of hereditary factors in predisposing individuals to venous blockage within the retina. This investigation focuses on evaluating the application of molecular genetic profiling to determine susceptibility to retinal vascular compromise. By detecting specific sequence variations and inherited alterations affecting coagulation and vascular integrity, clinicians can stratify risk prior to clinical onset, enabling personalized monitoring and early therapeutic intervention. Integrating genetic assessment into routine ophthalmic evaluation enhances predictive accuracy, facilitates preventive strategies, and supports individualized decision-making to mitigate vision-threatening events. Retinal vein occlusion (RVO) is a significant cause of visual impairment globally. Recent studies suggest that genetic predisposition plays an important role in the development of RVO. This study aims to evaluate the role of clinical genetic analysis in predicting the risk of RVO. By identifying genetic markers and polymorphisms associated with thrombophilia and vascular disorders, early risk stratification and preventive measures can be implemented. The integration of genetic testing in clinical practice may enhance individualized patient care and reduce the incidence of RVO-related complications.